2022
DOI: 10.5194/acp-22-8473-2022
|View full text |Cite
|
Sign up to set email alerts
|

Understanding aerosol composition in a tropical inter-Andean valley impacted by agro-industrial and urban emissions

Abstract: Abstract. Agro-industrial areas are frequently affected by various sources of atmospheric pollutants that have a negative impact on public health and ecosystems. However, air quality in these areas is infrequently monitored because of their smaller population compared to large cities, especially in developing countries. The Cauca River valley (CRV) is an agro-industrial region in southwestern Colombia, where a large fraction of the area is devoted to sugarcane and livestock production. The CRV is also affected… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…There one would expect important particle emissions not only from the principal road with 10 000 -11 000 vehicles per day that runs north-south in the valley just east of Vijes, but also from industrial and agricultural emissions taking place nearby in the valley. The Cauca River Valley is a center for sugarcane cultivation and the pre-harvest burning of sugar cane fields is an important contributor of PM concentrations in the valley (Mateus-Fontecha et al, 2022).…”
Section: Dispersion Model and Emission Inventory For Industrial Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…There one would expect important particle emissions not only from the principal road with 10 000 -11 000 vehicles per day that runs north-south in the valley just east of Vijes, but also from industrial and agricultural emissions taking place nearby in the valley. The Cauca River Valley is a center for sugarcane cultivation and the pre-harvest burning of sugar cane fields is an important contributor of PM concentrations in the valley (Mateus-Fontecha et al, 2022).…”
Section: Dispersion Model and Emission Inventory For Industrial Sourcesmentioning
confidence: 99%
“…1), where a large fraction of the area is devoted to sugarcane cultivation and production of its derivatives. A recent analysis of the PM2.5 aerosol composition in CRV (Mateus-Fontecha et al, 2022) showed a dominant fraction of organic matter (53%), both primary and secondary, followed by salts (20%, mostly ammonium sulphate), dust (9%) and elemental carbon (7%). The authors concluded that biomass burning was a persistent source, together with traffic and fuel combustion.…”
Section: Introductionmentioning
confidence: 99%
“…During wildfire events, the northern CdC experiences high temperatures, arid humidity levels, strong winds, and scant rainfall-factors that significantly promote wildfire development [9]. Notably, this region features shrubs tightly intertwined with agricultural endeavors (Figure 9), which have progressively expanded over time, augmenting the likelihood of wildfire occurrence as farmers resort to controlled burns for harvesting purposes (e.g., [12,83]), or even to shift crop types, such as illegal crops [8]. Notably, this evolving agricultural landscape has been shaped by both local dynamics and national policies enacted by the government, which have precipitated the expansion of Caqueta's agricultural frontier.…”
Section: Land Cover Analysismentioning
confidence: 99%
“…These aerosol flux levels are comparable to those in polluted urban (Pachón et al, 2018) or industrial areas. Finer particles, usually measured as PM2.5 (aerodynamic diameter <2.5 µm), are also emitted by operations on soils, diesel combustion for mechanization, and burning of biomass, including for land preparation and pre-harvest and crop residue management practices (Mateus-Fontecha et al, 2022). Diesel and biomass burning particles are mostly carbonaceous (soot and organic) and frequently toxic.…”
Section: Introductionmentioning
confidence: 99%